The pavements cost due to traffic overloads - Pais, Jorge C. (2019)
The traffic on roads is characterised by a large number of different vehicle types; these vehicles are considered in the pavement design by converting their effects through the use of truck factors. The truck factors transform the damage applied by the various axle types and loads to a standard axle. However, there is a considerable number of vehicles that travel with axle loads above the maximum legal limit. These axles/vehicles cause significant damage to the pavements, which increases the pavement construction and rehabilitation cost. This paper investigates the impact of overloaded vehicles using a vehicle weight database by examining the truck factors for different vehicle categories. The study concluded that overloaded vehicles increase pavement damage and life cycle costs by about 30% compared to the cost of the same vehicles with legal loads.